Implementing an ecosystem oceanography program to increase capacity and preparedness for dynamic ocean management and fishery challenges - Wells, Brian K.; Santora, Jarrod A. (Frontiers in Marine Science, 2023)
Building resilience in coastal resources and related communities is improved by a holistic ecosystem research approach for integrating socioecological system components; a key challenge in this process is capturing dynamic interactions between components. We present an application of ecosystem oceanography to address goals of marine conservation and management, including climate readiness and supporting a blue economy. Treating the ecosystem as the sample unit is fundamental to our research program. Specifically, spatiotemporal structure of relationships among taxa themselves is the study subject, not the individual members. Our approach outlines four steps toward successful implementation: 1) Build a conceptual ecosystem-oceanography model informed by previous science and human dimensions research to test hypotheses and identify gaps in our understanding; 2) Design survey and adaptive monitoring efforts, including data sharing protocols, to capture the spatiotemporal processes of ecosystem structure; 3) Use diet data and spatiotemporal variability in trophic interactions to quantify processes influencing ecosystem function, including persistent hotspots of abundance, biodiversity, and trophic transfer; 4) Link empirically-determined processes to improve parameterization of biophysical models to enable evaluation of ecosystem structure and functionality retrospectively and prospectively. Accomplishing these objectives requires a transdisciplinary team and will enable evaluation of specific management goals, develop indicators for tracking progress towards meeting them, and carry out scenario evaluation under near-term and long-term scenarios that explore key uncertainties (e.g., future climate and policy directions). We apply this four-step approach to identify key drivers for recent ecosystem and fishery surprises in the California Current Ecosystem. We propose this approach offers a means for anticipating future ecosystem states and increasing preparedness and capacity to overcome fishery surprises, and in doing so supporting the development of management approaches that are robust to uncertainty.